(untitled) (Journal of the College of Basic Education, 2025)
The research is concerned with studying the strategy of innovation and creativity in the design of the contemporary industrial product. The research problem was defined by the following question: Will the strategy of innovation and creativity be the basis upon which the design process of the contemporary industrial product is built, both formally and functionally, to become one of the foundations of the design process of the contemporary industrial product? The aim of the research is to identify the most important trends in the designs of contemporary industrial products according to the strategy of innovation and creativity. The research included a theoretical framework, the first section: the strategy of innovation in the design of the contemporary industrial product, the second section, the strategy of creativity in the design of the contemporary industrial product. The research followed the descriptive analytical approach, and the sample was chosen intentionally, representing the strategy of innovation and creativity and their role in the design of the contemporary industrial product, and the research reached the most important results. Of which The focus was clear on adopting innovation and creativity by adopting modern technologies in all models, as well as employing types of artificial intelligence according to the necessities of the work of each device. The most important conclusions were that types of innovation and creativity have characteristics and features that can be employed in industrial design in general and contemporary home appliance design in particular. The research concluded with suggestions and recommendations